Cytological and cultural evaluation of abnormal vaginal discharge in pregnancy and its co-relation with maternal and neonatal outcome - Khairnar, Vaibhav Suresh; Waikar, Manjushri Ravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy represents a risk factor in the occurrence of vaginal infection. This study was undertaken to define the persistence of vaginal flora in 280 pregnant women at 14 to 34 weeks’ gestation and to evaluate the role of cytology in diagnosis of vaginal infections. It aims to study the maternal and neonatal outcome in pregnancy with vaginal discharge. Methods: High vaginal swab samples and data on epidemiological characteristics were collected from 280 pregnant women between 14-34 weeks with complaints of abnormal vaginal discharge at booking clinic of Indira Gandhi Government Medical College, Nagpur. Vaginal swab was collected and sent to laboratory for further investigation to establish etiological diagnosis. After diagnosis by vaginal swab report, subjects were treated with the specific treatment to individual infection. Subjects were followed up during antenatal period for complications. A birth weight of delivered baby was noted. The data was analysed using software Graph Pad in stat 3. Results: The incidence of abnormal vaginal discharge in pregnancy was 23.9% in one year. The frequency of abnormal discharge was 53% among those aged 20-24 years (97/183), 49.2% in primigravida (65/132). Pain in lower abdomen and back was the most common symptoms i.e. 88.19% in Cases, while 17.36% had vulval pruritus and 14.58% had dysuria. Conclusions: This study recommend that women complaining of vaginal discharge in pregnancy should be evaluated for infections. this study supports CDC-P recommendation as all women who have symptomatic vaginitis, should be treated regardless of pregnancy status.